PROVISION OF SHELL SKIN FLOUR IN RANSUM TO THE EXTERNAL OFFAL PERCENTAGE OF ISA BROWN CHICKEN AGE 100 WEEKS - H. S., Raillah; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
The aim of this study was to determine the external percentage of 100 week old Isa Brown chickens that were given commercial feed with the addition of shellfish flour. The chickens used were 100 Isa Brown chickens aged 100 weeks. The experimental design used was a completely randomized design (CRD) with 4 treatments, where each treatment used 5 replications and each replication used 5 Isa Brown chickens. The ration treatments given to chickens were: commercial rations (P0), commercial rations plus 1% shellfish (P1), commercial rations plus 2% shellfish flour (P2) and commercial rations plus 3% shellfish flour (P3). The variables observed were the percentage of external offal (head, neck, legs, blood and hair). The results showed that the provision of commercial rations with the addition of shellfish flour 1%, 2% and 3% to the percentage of external external (head, neck, legs, blood and feathers) was not significantly different (P> 0.05). The conclusion from this study is that rations with the addition of 1%, 2%, and 3% of shellfish flour in commercial rations did not affect the percentage of external offal (head, neck, legs, feathers and blood) of 100 week old Isa Brown chickens. Keywords : Shellfish flour, external offal percentage, isa brown chicken